Critical pedagogy in dark times (Praxis Educativa, 2014)
The social benefits and rights granted by the welfare state are being dismantled by the forces of neoliberalism. That is why educators need to develop forms of critical pedagogy that can challenge them. A critical pedagogy as a project of insurgent democracy that can analyze the relations between knowledge, authority and power, committed to the responsibility of teachers as public intellectuals, in favor of an educated hope that offers critical knowledge linked to a democratic social change.